Catching the wave - Muckenfuss, M. (Swimming Technique, 1990)
This is an interview with Josef Nagy, coach of Mike Barrowman of the USA, current world-record holder in 200-m breaststroke. The article attributes Nagy as being the "inventor" of this stroke although that is highly unlikely (Canadian coaches would dispute it strongly). The central theme describing the action as a wave-motion is a speculative explanation that discounts the restrictions of anatomy that cause accommodations in swimming movements. Particular importance is given to the lunge forward along the top of the water. That action has two distinct and real advantages. 1.It accentuates the kick backward by adding a reaction force to the leg movement. 2.It accentuates streamlining, minimizes the time in a non-streamlined position, and keeps the swimmer on the surface of the water (where resistance is lower than under the water) for a slightly longer time (the extra force creates an accentuated hydroplane effect causing the swimmer to "stay up" longer than in a non-lunge action). Implications: The teaching technique of following a wave action is a good instructional method for minimizing frontal and eddy resistance in the stroke. The major contribution of this form of stroke is its emphasis on streamlining and the additional power that is developed through the wave action that travels down the body resulting in an enhanced kicking action.